UPAYA PENINGKATAN HASIL BELAJAR PENGANTAR AKUNTANSI DENGAN PENERAPAN ROLE PLAYING BERBANTUAN VIDEO - Azis, Abdul; -, Susilaningsih; Ivada, Elvia (Tata Arta : Jurnal Pendidikan Akuntansi, 2016)
ABSTRACTThe objective of this research is to investigate whether the application of video media-assisted role playing learning method can improve the learning result in Accounting of the students in Grade X Accounting 2 of Mumpuni State Vocational High School in Academic Year 2015/2016. This research used the classroom action research with two cycles. Each cycle consisted of four phases, namely: planning, implementation, observation, and reflection. The subjects of research were all of the students as many as 32 in Grade X Accounting 2 of the school. It was conducted in collaboration with the Introduction to Accounting subject matter teacher. Its data were collected through cognitive test; affective questionnaire; and psychomotor observation sheet. The result of research shows that the application of video media assisted role playing learning method in the Introduction to Accounting subject matter can improve the learning result in Accounting of the students in Grade X Accounting 2 of Mumpuni State Vocational High School in Academic Year 2015/2016 as indicated by the following: 1) The number of students who fulfilled the minimal learning completeness criterion for the affective aspect increased. In Pre-cycle, the number of students who fulfilled the minimal learning completeness criterion was (87.5%). Following the implementation, it became (93.75%) in Cycle I and (96.88%) in Cycle II. 2) The number of students who fulfilled the minimal learning completeness criterion for the cognitive aspect also increased. In Pre-cycle, the number of students who fulfilled the minimal learning completeness criterion was (25%). Following the implementation, it became (62.5%) in Cycle I and (84.38%) in Cycle II. 3) The number of students who fulfilled the minimal learning completeness criterion for the psychomotor aspect increased. In Cycle I, the number of students who fulfilled the minimal learning completeness criterion was (71.88%). Following the implementation, it became (93.75%) in Cycle II.Keywords: Learning method, learning media, learning result Â ABSTRAKPenelitian ini bertujuan untuk mengetahui apakah penerapan role playing berbantuan media video dapat meningkatkan hasil belajar akuntansi siswa kelas X Akuntansi 2 SMK Mumpuni* tahun ajaran 2015/2016. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan sebanyak 2 siklus. Masing-masing siklus dilaksanakan dalam empat tahapan, yaitu (1) perencanaan tindakan, (2) pelaksanaan tindakan, (3) pengamatan atau observasi dan (4) refleksi. Subjek penelitian ini adalah seluruh siswa kelas X Akuntansi 2 SMK Mumpuni* tahun ajaran 2015/2016 sebanyak 32 siswa. Penelitian ini dilakukan secara kolaborasi dengan guru mata pelajaran pengantar akuntansi. Penelitian ini menggunakan tiga teknik pengumpulan data yaitu (1) tes kognitif, (2) angket afektif, dan (3) lembar observasi psikomotorik. Teknik uji validitas data dalam penelitian ini menggunakan validitas isi. Data penelitian dianalisis secara deskriptif kualitatif. Hasil penelitian adalah bahwa penerapan metode pembelajaran role playing berbantuan video dapat meningkatkan hasil belajar siswa kelas X Akuntansi 2 SMK Mumpuni* tahun ajaran 2015/2016 pada mata pelajaran pengantar akuntansi. Hal tersebut dapat dilihat dari hasil penelitian sebagai berikut: (1) Hasil belajar afektif menunjukkan peningkatan dari 87,5% pada pratindakan, 93,75% pada siklus I dan pada siklus II menjadi 96,88%. (2) Hasil belajar kognitif menunjukkan peningkatan dari 25% pada pratindakan, 62,5% pada siklus I dan pada siklus II menjadi 84,38%. (3) Hasil belajar psikomotorik menunjukkan peningkatan dari 71,88% pada siklus I dan pada siklus II menjadi 93,75%.Kata kunci: metode pembelajaran, media pembelajaran, hasil belajar